Impacts of tree species admixing on soil carbon and soil properties in boreal conifer-dominated forests: Evidence from multiple datasets - Anna Repo; Päivi Soronen; Timo Domisch; Saija Huuskonen; Hannu Ilvesniemi; Aleksi Lehtonen; Jari Miina; Mari Myllymäki; Aino Smolander (Forest Ecology and Management, 2026)

A novel approach for assessing the importance of forest ecosystem services using indicators of potential and demand - Tina Simončič; Petra Grošelj; Adriano Mazziotta; Emin Zeki Başkent; Kyle Eyvindson; Henn Korjus; Eneli Põldveer; Sari Pynnönen; Grzegorz Rączka; Anna Repo; Andrej Bončina (Ecosystem Services, 2026)

3D-printed polyamide-H2TiO3 composite for selective lithium adsorption: Insights from experimental and theoretical dynamic simulations studies - Ekaterina Bandina; Mohammed Elkabous; Anna Iurchenkova; Youssef El Ouardi; Eveliina Repo (Minerals Engineering, 2025)

Assessing the impact of private forest owner preferences on the supply of ecosystem services - Adriano Mazziotta; Kyle Eyvindson; Jérémy Cours; Rémi Duflot; Anna Repo; Mari Selkimäki; Tuomo Takala; María Triviño; Mikko Mönkkönen (Journal of Environmental Management, 2025)

ForestScope: Comprehensive tool for analysing soil, climate, and stand data in forest ecosystems - Mahdi (André) Nakhavali; Andrey Lessa Derci Augustynczik; Anna Repo; Elia Vangi; Petr Havlík (Ecological Modelling, 2025)

Contrasting forest management strategies: Impacts on biodiversity and ecosystem services under changing climate and disturbance regimes - Anna Repo; Katharina Albrich; Aapo Jantunen; Juha Aalto; Ilari Lehtonen; Juha Honkaniemi (Journal of Environmental Management, 2024)

Future supply of boreal forest ecosystem services is driven by management rather than by climate change - María Triviño; Alejandra Morán‐Ordoñez; Kyle Eyvindson; Clemens Blattert; Daniel Burgas; Anna Repo; Tähti Pohjanmies; Lluís Brotons; Tord Snäll; Mikko Mönkkönen (Global Change Biology, 2023)
Forests provide a wide variety of ecosystem services (ES) to society. The boreal biome is experiencing the highest rates of warming on the planet and increasing demand for forest products. To foresee how to maximize the adaptation of boreal forests to future warmer conditions and growing demands of forest products, we need a better understanding of the relative importance of forest management and climate change on the supply of ecosystem services. Here, using Finland as a boreal forest case study, we assessed the potential supply of a wide range of ES (timber, bilberry, cowberry, mushrooms, carbon storage, scenic beauty, species habitat availability and deadwood) given seven management regimes and four climate change scenarios. We used the forest simulator SIMO to project forest dynamics for 100 years into the future (2016–2116) and estimate the potential supply of each service using published models. Then, we tested the relative importance of management and climate change as drivers of the future supply of these services using generalized linear mixed models. Our results show that the effects of management on the future supply of these ES were, on average, 11 times higher than the effects of climate change across all services, but greatly differed among them (from 0.53 to 24 times higher for timber and cowberry, respectively). Notably, the importance of these drivers substantially differed among biogeographical zones within the boreal biome. The effects of climate change were 1.6 times higher in northern Finland than in southern Finland, whereas the effects of management were the opposite—they were three times higher in the south compared to the north. We conclude that new guidelines for adapting forests to global change should account for regional differences and the variation in the effects of climate change and management on different forest ES.

Landowner preferences and conservation prioritization: response to Nielsen et al. - Kyle Eyvindson; Anna Repo; Daniel Burgas; Mikko Mönkkönen (Conservation Biology, 2017)
Article impact statement : Incorporating landowner preferences in prioritization schemes may not improve conservation efficiency.

Assessment of frost damage in mycorrhizal and non-mycorrhizal roots of Scots pine seedlings using classification analysis of their electrical impedance spectra - Tapani Repo; Anna Korhonen; Tarja Lehto; Raimo Silvennoinen (Trees, 2016)

Frost hardiness of mycorrhizal and non-mycorrhizal Scots pine under two fertilization treatments - Anna Korhonen; Tarja Lehto; Tapani Repo (Mycorrhiza, 2015)

Frost hardiness of mycorrhizal (Hebeloma sp.) and non-mycorrhizal Scots pine roots - Anna Korhonen; Tarja Lehto; Tapani Repo (Mycorrhiza, 2013)

Direct Compression of Cellulose and Lignin Isolated by a New Catalytic Treatment - Anna Penkina; Osmo Antikainen; Maija Hakola; Sirpa Vuorinen; Timo Repo; Jouko Yliruusi; Peep Veski; Karin Kogermann; Jyrki Heinämäki (AAPS PharmSciTech, 2013)